Implementation of a Lightweight and Portable Horn Antenna Using 3-D Printing Technology - Serhan Yamaçlı (Journal of Advanced Research in Natural and Applied Sciences)
In this study, a horn antenna operating at 5.8GHz centre frequency, which is an ISM operating frequency, is de-signed and manufactured. The novelty of the antenna is that it is produced using a 3D printer with a conductive filament containing carbon nanotube particles. The geometric dimensions of the antenna were calculated by means of an antenna design software. Then, the size of the radiating element of the antenna was optimized to set the centre frequency to 5.8GHz. It has been verified by electromagnetic simulations that the designed antenna exhibits this centre frequency. Then, the designed antenna geometry was sketched in a 3-dimensional drawing program and made ready for printing. This antenna was fabricated on an Ultimaker 3D printer with a PLA fila-ment containing conductive carbon nanotubes. The radiation element of the antenna and the SMA connector were finally attached to the printed antenna. The frequency response of the antenna is then measured using a vector network analyser and it has been shown that the produced pyramidal horn antenna works in the desired frequency band. The printed antenna has the desired frequency characteristic without the need for any additional coating or conductive spray thanks to the PLA filament containing conductive carbon nanotubes. The produced antenna has a weight of only 64.53 grams, including the SMA connector and the radiation element. The proposed lightweight and practical horn antenna design concept may have important applications considering the advances and needs of mobile defence and telecommunication systems.